Endoluminal Cooling of the Esophagus during Percutaneous Thermal Ablation for Juxtaesophageal Liver Neoplasm: Two Cases - Chihiro Itou; Yasuaki Arai; Miyuki Sone; Shunsuke Sugawara (The Arab Journal of Interventional Radiology)
Thermal injury to the surrounding hollow organs should be avoided during thermal ablation therapy. Although this type of injury is rare, severe complications, such as perforation or stricture, have been reported. Despite the development of various adjunctive thermoprotection techniques, there are a few reports of their use for protecting the esophagus during liver ablation therapy. Endoluminal irrigation is a well-known technique for protecting hollow organs, such as the biliary tract, renal pelvis, ureter, and rectum; however, it is used infrequently for avoiding thermal injury to the esophagus. There may be hesitation in treating juxtaesophageal liver tumors with conventional ultrasound-guided ablation because the location restricts the ultrasonic window due to the poor visibility. We successfully treated two consecutive cases of juxtaesophageal liver tumor with computed tomography-guided ablation by applying endoluminal irrigation and cooling via a 12-French nasal feeding tube placed in the lower esophagus.